Central Positional Nystagmus: A Systematic Literature Review - Macdonald, Nora K.; Kaski, Diego; Saman, Yougan; Al-Shaikh Sulaiman, Amal; Anwer, Amal; Bamiou, Doris-Eva (Frontiers in Neurology, 2017)
Objective: To provide a systematic review of the clinical and radiological features of lesion induced central positional nystagmus (CPN) and identify salient characteristics that differentiate central from peripheral positional nystagmus. Methods: Systematic literature search according to the Preferred Reporting items for Systematic Reviews and Meta-analysis (PRISMA). Results: A total of 82 patients from 28 studies met the PICOS criteria for inclusion. An atypical direction of nystagmus for the stimulated canal was reported in 97.5% patients during Dix-Hallpike (D-H) and 54.5% upon supine roll testing. Five types of CPN were identified during positional testing: positional horizontal nystagmus (pHN) (36.8%), positional down-beating nystagmus (pDBN) (29.2%), pure torsional nystagmus (2.1%), up-beating nystagmus (UBN) (2.1%), and a combination of the four profiles (29.9%). CPN was paroxysmal (<60 seconds) in 85% patients on straight head-hanging, 63.9% on D-H and 37.5% on supine roll, and had a latency <3 seconds upon positioning in 94.7% patients in which it was reported. Concurrent vertigo was reportedly present in 63.4% patients, and 48.8% demonstrated other neurological signs. Radiologically, in 74.4% there was mention of cerebellar involvement, isolated brainstem involvement in 8.5%, and 14.6% involved the IVth ventricle. Conclusions: Currently there is a lack of robust data on the clinical and radiological characteristics of CPN highlighting the need for better phenotyping of CPN to help differentiate this entity from peripheral causes of positional nystagmus. With increased awareness of CPN, particularly in the acute setting, we may see a change in the estimated prevalence of central positional nystagmus, and improved clinical markers to promptly identify the frequently sinister underlying causes.